2001
DOI: 10.1097/00000542-200109000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Total Intravenous Anesthesia with Propofol versus  Inhalation Anesthesia with Isoflurane–Nitrous Oxide

Abstract: Propofol TIVA results in a clinically relevant reduction of postoperative nausea and vomiting compared with isoflurane-nitrous oxide anesthesia (number needed to treat = 6). Both anesthetic techniques were otherwise similar. Anesthesia costs were more than three times greater for propofol TIVA, without economic gains from shorter stay in the postanesthesia care unit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
6
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 26 publications
6
109
6
7
Order By: Relevance
“…Foi recomendada a identificação de fatores de risco e a sua redução sempre que possível. Visser e col. demonstraram que o uso de propofol na indução e manutenção da anestesia reduz a incidência de NVPO precoce (primeiras 6 horas após a cirurgia) 23 . A incidência de NVPO diminui quando se evita o uso de anestésicos inalatórios ou óxido nitroso 24 .…”
Section: Identificação De Fatores De Risco Para Nvpounclassified
See 1 more Smart Citation
“…Foi recomendada a identificação de fatores de risco e a sua redução sempre que possível. Visser e col. demonstraram que o uso de propofol na indução e manutenção da anestesia reduz a incidência de NVPO precoce (primeiras 6 horas após a cirurgia) 23 . A incidência de NVPO diminui quando se evita o uso de anestésicos inalatórios ou óxido nitroso 24 .…”
Section: Identificação De Fatores De Risco Para Nvpounclassified
“…Whenever possible, it is recommended to identify risk factors and minimize them. Visser et al have shown that propofol for anesthetic induction and maintenance decreases the incidence of early PONV (first 6 postoperative hours) 23 . The incidence of PONV decreases when inhalational anesthetics or nitrous oxide are avoided 24 .…”
Section: Ponv Prevention and Treatmentmentioning
confidence: 99%
“…Although a rare condition, vomiting can occur without nausea (e.g., Visser, Hassink, Bonsel, Moen, & Kalkman, 2001). Nausea is not simply the result of a low level of stimulation to the emetic system, which if only increased in intensity would result in vomiting.…”
mentioning
confidence: 99%
“…However, the risks of PONV associated with total iv anesthesia (i.e., propofol-based anesthetic) appear to lower than that associated with inhalation anesthesia. 17 Recent data suggest that combinations of antiemetics administered prophylatically are more effective than either antiemetic administered alone, particularly in high-risk patients. 2 A multimodal approach to prevention of PONV includes use of combinations of droperidol 0.625-1 mg, 5-HT 3 antagonists (ondansetron 4 mg or dolasetron 12.5-5 mg), and dexamethasone 4-8 mg, as well as aggressive hydration, use of minimal doses of opioids, and aggressive pain control.…”
Section: Pulmonary Changesmentioning
confidence: 99%